Resection of infarcted upper lobe with reimplantation of the lower lobe allograft after initial bilateral full-sized lung transplantation: a case report - An-Lies Provoost; Paul De Leyn; Hans G.L. Van Veer; Lieven P. Depypere; Yanina Jansen; Robin Vos; Birgit Weynand; Sophie Pirenne; Dirk E. Van Raemdonck; Laurens J. Ceulemans (JHLT Open)
We describe the case of a patient with lobar-lung auto-reimplantation following bilateral lung transplantation because of vascular and bronchial anastomotic complications with upper lobe infarction. Pneumonectomy of the left allograft with ex-vivo upper lobectomy and lower lobe reimplantation was successfully performed, resulting in favorable short-term recovery and improving graft function at 7-month follow-up.